Analysis on motif of storage jar (TAJAU) in Iban community / Haslinda Md. Nazri. - Md. Nazri, Haslinda (2011)
This research is conducted based on the core problem that had occurred in Iban's cultural, especially among the new modern young generation. This generation seems to take for granted the beauties in Iban's history and try to leave their fundamental founded by their ancient generation before invaluable traditional art, of the storage jar. Religion factor considered as the major cause of this beautiful art washed out from Iban's life style. This storage jar with animal motif was not allowed to be practiced by the religious principals because it had strong connection with animism belief in paganism world. Beside that, there are too many types of storage jars around the world. Each traditional motif has its own meaning according to geographical factor and wearer's belief. This big question arouses deep interest for the researcher to explore and to reveal the secret world of storage jar. This research basically based on descriptive research. Descriptive research normally focuses on a certain case of interest. The object under study would be described on any aspect that researcher is interested in, and then it will be described in detail. Finally, this research is a medium in presenting the unique of tradition, custom and cultural of Iban society to other people, academically. This research also tried to stage up Iban society internationally as a group of people who appreciate their ancestors' life values into their young generation in modernization and globalization world.